Peningkatan Prestasi Belajar Siswa dalam Pembelajaran Fiqih melalui Kombinasi Metode Everyone Is A Teacher Here dan Team Quiz - Agus Nur Soleh; Isnaini , (LPPM IAINU Kebumen, 2019)
Efforts to increase learning achievement in learning Fiqh in madrasas through a combination of two methods, everyone is a teacher here with a team quiz. In addition to efforts to increase the learning of jurisprudence, this paper also aims to present an understanding that the two methods can be combined and can be used for the purpose of increasing learning achievement. This paper is an analytical description. The results are that: (1) the combination of the two methods can encourage students to be more able to understand the essence, meaning, and benefits of the learning process in fiqh learning, and (2) can be a stimulus and in turn can stimulate students to be more active in learning so that learning achievement students can increase in learning fiqh.